The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jiec.12759
|View full text |Cite
|
Sign up to set email alerts
|

Corporate and Product Carbon Footprint under Compound Hybrid Analysis: Application to a Spanish Timber Company

Abstract: The European Union (EU) is advancing steadily toward the stabilization of atmospheric greenhouse gas concentrations. Various sectors are now obliged to make reductions, and new policies based on the carbon footprint are being encouraged. However, voluntary reporting of so-called scope 3 emissions is hindering successful implementation of these policies. In this study, we present a tiered hybrid analysis to report emissions according to the ISO/TR 14069 standards and to obtain complete measures of scope 3 emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Future studies could also apply the proposed method to the Analytical AMNE database to trace the carbon footprints of overseas operations of Chinese listed companies. In addition, future studies could adopt the hybrid LCA method 35 , which combines EIO-LCA and process LCA, to reflect the difference in production technologies among listed companies.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could also apply the proposed method to the Analytical AMNE database to trace the carbon footprints of overseas operations of Chinese listed companies. In addition, future studies could adopt the hybrid LCA method 35 , which combines EIO-LCA and process LCA, to reflect the difference in production technologies among listed companies.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars further identified the currently voluntary nature of corporate scope 3 emission reporting as an inhibitor for scope 3 emission reduction. For example, Alvarez et al (2019) claim that because it is voluntary, many firms currently do not report their scope 3 emissions, which in turn slows down scope 3 emission reduction.…”
Section: Carbon Performancementioning
confidence: 99%
“…Vasquez et al (2015), Clabeaux et al (2020), Kulkarni (2019), and Robinson et al (2018) all conducted similar analyses on the advantages of a bottom‐up approach for calculating a university's carbon footprint and confirmed Brander's view. Alvarez et al (2019) analyzed the application of a compound hybrid analysis for the improvement of carbon footprint calculations as part of a case study of a Spanish timber firm. They found that their approach improves accuracy and efficiency, and reduces costs.…”
Section: The Literature On Scope 3 Emissionsmentioning
confidence: 99%
“…Besides, with product carbon footprints (PCFs) a tool has been developed in the field of industrial ecology which allows consumers to judge climate change-related impacts of products (e.g., Draucker et al, 2011;Lenzen, 2014). Drawing on Alvarez et al (2018), the PCF can be defined as an indicator measuring the direct and indirect green-house gas emissions caused by a specific product along its entire life cycle. Unlike most environmental labels, PCFs provide quantitative and not only qualitative environmental information.…”
Section: Introductionmentioning
confidence: 99%